Answer:
Step-by-step explanation:
![2x^{2} + x - 4 = 0\\](https://tex.z-dn.net/?f=2x%5E%7B2%7D%20%20%2B%20x%20-%204%20%3D%200%5C%5C)
divide by 2 throughout
![x^{2} + \frac{x}{2} = \frac{4}{2}](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%20%2B%20%5Cfrac%7Bx%7D%7B2%7D%20%20%3D%20%5Cfrac%7B4%7D%7B2%7D)
![x^{2} +2 * \frac{x}{4} +( \frac{1}{4}) ^{2} = 2 + ( \frac{1}{4}) ^{2}\\](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2B2%20%2A%20%5Cfrac%7Bx%7D%7B4%7D%20%2B%28%20%5Cfrac%7B1%7D%7B4%7D%29%20%5E%7B2%7D%20%20%3D%202%20%2B%20%28%20%5Cfrac%7B1%7D%7B4%7D%29%20%5E%7B2%7D%5C%5C)
![(x+\frac{1}{4} ^{2} ) = 2 + (\frac{1}{4} )^{2} \\](https://tex.z-dn.net/?f=%28x%2B%5Cfrac%7B1%7D%7B4%7D%20%5E%7B2%7D%20%29%20%3D%202%20%2B%20%28%5Cfrac%7B1%7D%7B4%7D%20%29%5E%7B2%7D%20%5C%5C)
Let the length of the shortest side be x, then the length of the second side is x + 4 and the length of the third side is 2x - 4.
Then, x + x + 4 + 2x - 4 = 52
4x = 52
x = 52/4 = 13
Therefore, the lengths of the sides of the triangle are: x = 13, x + 4 = 13 + 4 = 17 and 2x - 4 = 2(13) - 4 = 26 - 4 = 22.
i.e. 13, 17, 22
Answer: 51
Step-by-step explanation: (sqrt(2))^2 + 7^2
The squareroot and square cancel, leaving 2. 7^2=7*7=49
49+2=51
Answer:
3332 green beads
Step-by-step explanation:
Add 3 to -3 and -177 then divide -174 by6